First teratological case of the ocular pattern in the brown recluse spider genus Loxosceles Heineken & Lowe (Araneae, Sicariidae) - Taucare-Rios, Andres; Faundez, Eduardo; Brescovit, Antonio D. (My University, 2021)
An ocular malformation is described for the first time in the genus Loxosceles, specifically in a female of Loxosceles surca Gertsch. The specimen was collected at 3,540 m.a.s.l. in Tarapaca Region, Chile. It is the first record for this family and the first case of teratology described for spiders in this country.
Keywords: deformity; eye anomalies; teratology